Creep Properties of Mudstone Interlayer in Bedded Salt Rock Energy Storage Based on Multistage Creep Test: A Case Study of Huai'an Salt Mine, Jiangsu Province. (30th August 2022) - Chen, Jie; Chen, He; Wu, Fei; Jiang, Deyi; Zhang, Hao; Gao, Renbo; Ding, Bowen
Abstract : Salt rock is internationally recognized as an excellent medium for energy storage. However, most of the domestic salt mines are lacustrine laminated formations with mudstone interlayers, which have different creep characteristics to pure salt rocks. Therefore, in this paper, uniaxial compression creep tests were carried out on a mudstone interlayer in Huai'an, Jiangsu, China, and the multistage creep mechanical behavior of the mudstone interlayer was investigated using acoustic emission (AE) technology. The results show that at low stress levels, the axial deformation of the interlayer is greater than the lateral deformation. As the increase of the stress level, the lateral deformation becomes more significant, and the corresponding axial and lateral steady-state creep rates both exhibit nonlinear acceleration with the increase of the loading stress. In the initial loading stage of each stress level, the mudstone interlayer releases a large number of AE signals. After the creep stabilization, the AE signals decreased obviously, and a large number of AE signals were released at the last stress level. Based on the creep test data, an improved fractional viscoelastic-plastic model was fitted to it and compared with the Nishihara model. The applicability of the model was also tested, and the model was found to be a good description of the mudstone interlayer after oil erosion. The research results reflected the creep law of the mudstone interlayer to a certain extent and are expected to serve as a reference to studies on the long-term stability of the surrounding rock of a bedded salt rock energy storage.